The Role of the Cerebral Capillaries in Acute Ischemic Stroke: The Extended Penumbra Model. Issue 5 (May 2013) - Østergaard, Leif; Jespersen, Sune Nørhøj; Mouridsen, Kim; Mikkelsen, Irene Klærke; Jonsdottír, Kristjana Ýr; Tietze, Anna; Blicher, Jakob Udby; Aamand, Rasmus; Hjort, Niels; Iversen, Nina Kerting; Cai, Changsi; Hougaard, Kristina Dupont; et al.
The pathophysiology of cerebral ischemia is traditionally understood in relation to reductions in cerebral blood flow (CBF). However, a recent reanalysis of the flow-diffusion equation shows that increased capillary transit time heterogeneity (CTTH) can reduce the oxygen extraction efficacy in brain tissue for a given CBF. Changes in capillary morphology are typical of conditions predisposing to stroke and of experimental ischemia. Changes in capillary flow patterns have been observed by direct microscopy in animal models of ischemia and by indirect methods in humans stroke, but their metabolic significance remain unclear. We modeled the effects of progressive increases in CTTH on the way in which brain tissue can secure sufficient oxygen to meet its metabolic needs. Our analysis predicts that as CTTH increases, CBF responses to functional activation and to vasodilators must be suppressed to maintain sufficient tissue oxygenation. Reductions in CBF, increases in CTTH, and combinations thereof can seemingly trigger a critical lack of oxygen in brain tissue, and the restoration of capillary perfusion patterns therefore appears to be crucial for the restoration of the tissue oxygenation after ischemic episodes. In this review, we discuss the possible implications of these findings for the prevention, diagnosis, and treatment of acute stroke.